English consonant cluster pronunciation among Thai junior high school EFL students in an authentic classroom: Error patterns - Betri Ciandayani; Indawan Syahri; Rini Susanti (Institute of Information Technology and Social Science (IITSS), 2026)
This study examines English words containing consonant clusters that are most frequently mispronounced by Thai students learning English as a foreign language (EFL) and identifies the phonological patterns underlying these pronunciation errors. The study employs a descriptive qualitative design, supported by descriptive statistics to complement the phonological analysis. The study participants consisted of 21 junior high school students from Thailand who completed a speaking task comprising 15 target items (14 words and one phrase). The recordings were transcribed using the International Phonetic Alphabet (IPA) and analyzed to identify recurring pronunciation patterns. The findings indicate that words with initial consonant clusters posed the greatest difficulty in pronunciation. Specifically, all participants (100%) mispronounced five target words. Rather than making random errors, the learners consistently employed three phonological correction strategies: vowel insertion (epenthesis), consonant substitution, and modification of final consonants. This suggests the influence of Thai phonotactic constraints and first-language phonology on the production of consonant clusters in English. These findings provide classroom-based evidence of systematic transfer from the first language and highlight the need for explicit speech instruction focused on consonant clusters through activities such as auditory discrimination, minimal pair exercises, guided articulation practice, and contrastive analysis to improve students’ speech clarity.